Measuring aedes & breteau indices in determining dengue outbreak; a study in Kota Tinggi - Norzaher Ismail; Razali Maulod; Shamsul Azhar Shah; Nazarudin Safian (Penerbit Universiti Kebangsaan Malaysia, 2019)
Introduction Dengue fever, the most known vector-borne disease in the tropical and subtropical regions has become major public health concern worldwide. Rapid urbanization, increased population movement and poor public hygienic lifestyle contributed to the proliferated of high incidence of dengue fever in urban and semi urban areas. With the increasing trend of dengue cases and deaths, methods of dengue surveillance should be reevaluated in predicting dengue outbreak. Methods This study aimed to determine association between Aedes Index and Breteau Index with dengue outbreak in the district of Kota Tinggi, Johor. Results Total of 593 dengue cases in 2015 collected from Kota Tinggi Health Office. The study found that there were significant association between Aedes Index and Breteau Index with localities (p< 0.01) significant association between dengue outbreak incidence and low transmission of aedes indices (p<0.01). However these indices reported low sensitivity and specificity in predicting dengue outbreak in this area. Conclusions As dengue disease remains a major endemic in Malaysia, better surveillance index should be reconsider as the main surveillance for dengue disease.